Learner profiles in secondary education: Occurrence and relationship with performance and student characteristics. Issue 3 (4th May 2019) - Rogiers, Amélie; Merchie, Emmelien; Van Keer, Hilde
Abstract: The authors explore the occurrence of different learner profiles in secondary education, as well as their relationship with test performance and student characteristics. Based on a cluster analysis of 1, 931 secondary school students' self-reported text-learning strategy use and study traces, the authors identified and validated four distinct learner profiles: integrated strategy users, information organizers, mental learners, and limited strategy users. Integrated strategy users engaged in different text-learning strategies and obtained the highest scores on the performance test. Limited strategy users generally used only a limited number of text-learning strategies and scored the lowest. In addition, a significant difference was established in gender and reading ability distribution across learner profiles, but home language distribution was not found to be significant.